Impact of fatigue on the balance and reaction time of amateur padel athletes - Bourara, A; Nemeth, Z; Methnani, J; Wilhelm, M. (Asian Journal of Sports Medicine, 2023)
Background: Physical features, such as body balance and reaction time, can significantly influence the overall performance of Padel's professional athletes.